Study the Structure Properties of Semiconductor Film Multilayered - Al-Atraqji, Hind Basil; Al.Kaisy, Hanaa Arer (Al-Khwarizmi Engineering Journal, 2010)
In this research was study the effect of increasing the number of layers of the semiconductor films as PbS on the average grain sizes and illustrate the relationship between the increase in the average grain size and thickness of the membrane, and membrane was prepared using the easy and simple and does not need the complexity of which is that the chemical bath , and from an X-ray diffraction found that the material and the installation of a random cubic and when increasing the number of layers deposited note the emergence of a number of vertices of a substance and PbS at different levels but the level is more severe (200) as well as the value is calculated optical energy gap and found to be not affected by increase thickness and from this value can be determined  the  applications of semiconductor materials and elected on the basis of Article absorbed optical radiation that incident on them.